Trickling Down: The Relationship Between Economic Growth and the Extent of Poverty Among American Families - Anderson, W. H. Locke (Quarterly Journal of Economics, 1964)
Introduction, 511. — Income growth and distribution, 513. — The incidence of poverty and its changes, 514. — Measuring the poverty curve, 515. — Subgroup poverty curves, 517. — Poverty status of population subgroups, 1959, 519. — The elasticity of subgroup incomes with respect to economic growth, 521. — Conclusions, 523.